Adverse effects associated with the use of anabolic agents in athletes: systematic review - Urios López, Ricardo; Sanz-Valero, Javier (Ars Pharmaceutica (Internet), 2018)
Objective: Review the scientific documentation on the adverse effects of anabolic agents in adults who practice sports. Method: Descriptive cross-sectional study and critical analysis of the works recovered through systematic review. The data were obtained from direct consultation and access, via the Internet, to the following bibliographic databases in the field of health sciences: MEDLINE (vía PubMed), The Cochrane Library, Scopus, Cumulative Index to Nursing and Allied Health Literature (CINHAL), Web of Science y PsycINFO until October 2017. The use of Descriptors was considered appropriate «Sports», «Anabolic Agents/Adverse effects», using the filters: «Clinical Trial», «Comparative Study», «Humans» y «Adult:19+years». Results: Of the 108 recovered references, after applying the inclusion and exclusion criteria, 15 articles were selected for review. One job was found in the bibliographic listings. By evaluating the quality of selected articles for review using the CONSORT questionnaire, scores ranged from 11,5 to 15,5 on a maximum score of 25. Conclusions: The revised work presented a higher obsolescence than expected in the area of health sciences. The articles were written preferably in English. It was observed, that the AAS had adverse effects, especially at the cardiovascular, behavioral level and appearance of side effects associated with the consumption of anabolic agents. Although there are discrepancies between the magnitude of them at the cardiovascular level and their potential damage.